2019
DOI: 10.1248/bpb.b18-00800
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Treatment with α-Lipoic Acid Improves Endothelium-Dependent Vasorelaxation of Aortas in High-Fat Diet-Fed Mice

Abstract: α-Lipoic acid (ALA) is used as a dietary supplement and known as an anti-oxidant. The present study aimed to examine whether ALA improves endothelial dysfunction in high-fat diet-fed obese mice. After feeding a high-fat diet to Institute of Cancer Research (ICR) mice for 4 weeks, the mice were maintained with a high-fat diet (group HF) or a high-fat diet containing ALA (25 mg/d, group HF ALA) for an additional 20 weeks. Age-matched normal diet-fed mice were also used (group Normal). Chronic oral treatment with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…However, endothelial dysfunction in KKAy-Normal mice did not improve following POA administration. Although we have reported on several substances that alter endothelial function in the absence of decreased plasma glucose levels [10,20,29], POA may not improve endothelial function despite its ability to decrease blood glucose levels. On the other hand, POA-induced changes were observed in the aortic contractile response (Figs.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, endothelial dysfunction in KKAy-Normal mice did not improve following POA administration. Although we have reported on several substances that alter endothelial function in the absence of decreased plasma glucose levels [10,20,29], POA may not improve endothelial function despite its ability to decrease blood glucose levels. On the other hand, POA-induced changes were observed in the aortic contractile response (Figs.…”
Section: Discussionmentioning
confidence: 84%
“…Aortic vascular function was measured as previously described [19][20][21]. Brie y, the thoracic aorta was quickly isolated and immersed in oxygenated, modi ed ice-cold bicarbonate-buffered physiologic salt solution (PSS; containing 137 mM NaCl, 4.73 mM KCl, 1.2 mM MgSO 4 , 0.025 mM EDTA, 1.2 mM KH 2 PO 4 , 2.5 mM CaCl 2 , and 11.1 mM glucose).…”
Section: Measurement Of Isometric Forcementioning
confidence: 99%
“…However, endothelial dysfunction in KKAy mice did not improve following POA administration. Although we have reported on several substances that alter endothelial function in the absence of decreased plasma glucose levels [ 14 , 28 , 40 ], POA may not improve endothelial function despite its ability to decrease blood glucose levels. On the other hand, POA-induced changes were observed in the aortic contractile response (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Clonidine extended release treatment is effective in children and adolescents with ADHD or Tourette’s disorder [ 175 ]. Analysis of vascular response in normal mice showed that the clonidine-induced relaxation was reduced by inhibiting the PI3K/Akt/eNOS pathway [ 176 ]. Modafinil is an effective drug for the treatment of ADHD [ 177 ].…”
Section: Natural and Synthetic Pi3k Signaling Pathway Modulatorsmentioning
confidence: 99%